Kesadaran Pemberian ASI pada Anak di IKN: Memberdayakan Ibu di Semoi Dua Melalui PERISAI - Selanno, Marcella Mandy; Sari, Rinda Rahma (Mulawarman International Conference on Tropical Public Health, 2025)
Background : In the Semoi Dua Village Area, Hamlet 1, has several health problems, especially in infant nutritional health, according to the results of interviews that have been conducted, it was found that some respondents still do not fully know the benefits of Early Breastfeeding Initiation (IMD) and breastfeeding babies. The percentage of Early Breastfeeding Initiation (IMD) in Semoi Dua Village, Hamlet 1 is only 33.3%, and the percentage of exclusive breastfeeding is only 50%. Objective : PERISAI (Caring for Breastfeeding in Babies) is a program carried out to increase the knowledge of mothers about the importance of Early Breastfeeding Initiation (IMD) and breastfeeding through counseling activities, while this counseling activity is also equipped with leaflets that have been made through canva media, which contains points about the importance of Early Breastfeeding Initiation (IMD) and breastfeeding, so that it can make it easier for participants to understand the material provided during the activity counseling took place. With the PERISAI (Care for Breastfeeding for Babies) program, it aims to make mothers better understand the importance of Early Breastfeeding Initiation (IMD) and breastfeeding, so that babies can receive antibodies through Colostrum breast milk, also help the development of the baby's brain, and help digest nutrients more efficiently, also contain a lot of carbohydrates, vitamins, proteins, and fats and can save costs compared to giving formula milk to babies. Research Methods/ Implementation Methods : The PERISAI (Care for Breastfeeding for Babies) program was held at Posyandu Komala Jaya, Semoi Dua Village, Hamlet 1 on Wednesday, July 17, 2024 from 09.00 to 11.00 WITA, with a target of 15 program participants with the criteria of breastfeeding mothers from Posyandu Komala Jaya and Posyandu Abadi Jaya. The stages in the PERISAI (Care for Breastfeeding for Babies) activities, including preparation, counseling, breastfeeding position practice, discussions and games. Results : To calculate the increase in knowledge of program participants is to use the summative evaluation method, namely the provision of pre-test and post-test as many as 5 questions, then the results of the pre-test and post-test obtained are analyzed using the Wilcoxon Test. The result of Sig. (2-tailed) was obtained of 0.004. This shows that the value of Sig. (2-tailed) is 0.004 < Sig. 0.005. Conclusion/Lesson Learned : There is a significant difference between the pre-test score and the post- test score. So it can be concluded that participants have increased their knowledge about the benefits of Early Breastfeeding Initiation (IMD) and breastfeeding babies.